Investigation of small oscillations of a two-axle trailer - Polyashenko, S.; Iesipov, O.; Olyanich, L. (My University, 2020)
The conditions of stable movement of a tractor train and the factors influencing the nature of oscillating movement of trailers are analyzed. The location of the cargo on the platform and the speed of the tractor train have a significant impact on the nature of the oscillating motion of trailers. These performance factors cannot be chosen arbitrarily, they must be coordinated with other parameters of the trailer.
Polyashenko S. Investigation of small oscillations of a two-axle trailer | S. Polyashenko , O. Iesipov , L. Olyanich // Fundamental and applied research in the modern world. Abstracts of V International Scientific and Practical Conference. - Boston, USA. 2020. Pp. 183-189.
Keywords: стійкість руху, тракторний поїзд, двовісний причіп, коефіцієнт лобового опору; stability of movement, tractor train, two-axle trailer, drag coefficient; устойчивость движения, тракторный поезд, двухосный прицеп, коэффициент лобового сопротивления